1975
DOI: 10.1136/pgmj.51.598.527
|View full text |Cite
|
Sign up to set email alerts
|

Renal retention of sodium in cirrhosis and fulminant hepatic failure

Abstract: Summary Abnormal renal retention of sodium is a characteristic finding in both cirrhosis and fulminant hepatic failure. In cirrhosis the pathogenesis varies according to the level of renal perfusion. When this is normal, hyperaldosteronism is probably the most important factor and this results from an increased release of renin by the kidney. The stimulus to the latter may be a shunting of blood from the outer cortical to juxtamedullary nephrons, although there is no direct relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1978
1978
2005
2005

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Second, renin secretion in cirrhosis may be also mediated by the adrenergic system, since propranolol, a &blocking agent, markedly reduces plasma renin activity in patients with cirrhosis and ascites [24]. Another possibility, already suggested, is that renin release could be induced by a redistribution of blood flow withn the renal cortex [25]. It has been shown that there is more reninin the superficial than in the juxtamedullary nephrons [26-281; a redistribution of renal blood flow to the juxtamedullary nephrons could lead to ischaemia of the outer cortex, stimulating renin release without decreasing the total glomerular filtration rate or the renal plasma flow.…”
Section: Discussionmentioning
confidence: 99%
“…Second, renin secretion in cirrhosis may be also mediated by the adrenergic system, since propranolol, a &blocking agent, markedly reduces plasma renin activity in patients with cirrhosis and ascites [24]. Another possibility, already suggested, is that renin release could be induced by a redistribution of blood flow withn the renal cortex [25]. It has been shown that there is more reninin the superficial than in the juxtamedullary nephrons [26-281; a redistribution of renal blood flow to the juxtamedullary nephrons could lead to ischaemia of the outer cortex, stimulating renin release without decreasing the total glomerular filtration rate or the renal plasma flow.…”
Section: Discussionmentioning
confidence: 99%
“…which promotes per se increased sodium reabsorption at the proximal nephron level through aldosteroneindependent mechanisms [13].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional viewpoint held is that aldosterone is a major determinant of sodium reten tion [5,42,43]. Thus, several investigators have reported progressive loss of ascites in cirrhotic patients following adrenalectomy [18,29], Wilkinson el al.…”
Section: Role Of Hyperaldosteronismmentioning
confidence: 99%